ChemInform Abstract: Concise Synthesis of the Multiply Oxygenated ABC‐Ring System of the Dihydro‐β‐agarofurans. Issue 5 (4th February 2014) - Ishiyama, Tomochika; Urabe, Daisuke; Fujisawa, Hiroki; Inoue, Masayuki
Abstract Diels—Alder reactions of the lactones (I) and (II) is optimized with respect to selective production of the exo‐adduct (III) thus establishing the C5‐ and C10‐tetrasubstituted and C2‐alkoxy‐substituted stereocenter for the conversion to the ABC‐ring fragment (IV*) of dihydro‐β‐agarofurans.